1999
DOI: 10.1161/01.res.85.2.182
|View full text |Cite
|
Sign up to set email alerts
|

BTEB2, a Krüppel-Like Transcription Factor, Regulates Expression of the SMemb/Nonmuscle Myosin Heavy Chain B (SMemb/NMHC-B) Gene

Abstract: We have recently characterized the promoter region of the rabbit embryonic smooth muscle myosin heavy chain (SMemb/NMHC-B) gene and identified the 15-bp sequence, designated SE1, located at Ϫ105 from the transcriptional start site as an important regulatory element for its transcriptional activity in a smooth muscle cell (SMC) line. In this study, we attempted to isolate cDNA clones encoding for the transcription factors that control the expression of the SMemb gene through binding to this cis-regulatory eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
133
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(135 citation statements)
references
References 50 publications
2
133
0
Order By: Relevance
“…The monoclonal anti-BTEB2 antibody was a generous gift from Yamasa Corp. (Diagnostics Division, Chiba, Japan) and was raised against a carboxyl-terminal peptide antigen described previously (29). The polyclonal anti-GKLF antibody was purchased commercially (M-19X, Santa Cruz Biotechnology).…”
Section: Preparation Of Smc Nuclear Extracts and Electrophoretic Mobimentioning
confidence: 99%
See 2 more Smart Citations
“…The monoclonal anti-BTEB2 antibody was a generous gift from Yamasa Corp. (Diagnostics Division, Chiba, Japan) and was raised against a carboxyl-terminal peptide antigen described previously (29). The polyclonal anti-GKLF antibody was purchased commercially (M-19X, Santa Cruz Biotechnology).…”
Section: Preparation Of Smc Nuclear Extracts and Electrophoretic Mobimentioning
confidence: 99%
“…The GKLF-related Factor BTEB2 Transactivates SM22␣ Promoter Activity-Recent studies have implicated a possible role for the GKLF-related BTEB (basic transcriptional element-binding protein) factors in the transactivation of gene expression during SMC phenotypic modulation (29,47). To test whether BTEB2 might contribute to TGF-␤-dependent regulation of SM22␣ in vitro, multipotent embryonic 10T1/2 cells were transiently cotransfected with an SM22␣ promoter-lacZ reporter construct and a BTEB2-containing mammalian expression vector (pcDNA3/BTEB2) (Fig.…”
Section: Evidence For the Presence Of A Gklf-related Factor In The Tgmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous experiments have demonstrated that BTeB2 is down-regulated during aortic development and is re-induced after balloon injury (6), suggesting that BTeB2 may be involved in the development of neointimal formation. The present study demonstrated that the knockdown of BTeB2 significantly reduced balloon injury-induced neointimal formation, indicating that BTeB2 may serve as powerful stimulus of neointimal hyperplasia.…”
Section: Discussionmentioning
confidence: 96%
“…Basic transcription element-binding protein 2 (BTeB2), a transcription factor that binds Gc boxes, is preferentially expressed in dedifferentiated or activated SMcs (6). it has been reported that atherosclerotic lesions containing BTeB2-positive cells are associated with a higher risk of restenosis than BTeB2-negative lesions (7), suggesting that BTeB2 serves as a regulator of vascular SMc proliferation and phenotypic changes.…”
Section: Introductionmentioning
confidence: 99%